Valentinianism new studies - Markschies, Christoph Johannes 1962-; Thomassen, Einar 1951- (Leiden Boston Brill, 2020)
"Since Antiquity, the movement associated with Valentinus has been regarded as the most typical and the most representative exponent of "Gnosticism." Recent research has led to a new appraisal of Valentinianism as a distinct form of early Christianity that deserves to be understood in its own right. Valentinianism served as a catalyst for the development of mainstream Christian doctrine, exegesis and ritual. Its connections to contemporary forms of Platonism are being progressively uncovered. The present volume, edited by Christoph Markschies and Einar Thomassen, shows the current state of research on Valentinianism, offering contributions by leading experts about the history of the movement, contested aspects of Valentinian doctrine, and the use and interpretation of the New Testament by the Valentinians"--
Includes bibliographical references
Beiträge teilweise englisch, teilweise deutsch, teilweise französisch
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Valentinians; Konferenzschrift